Textbook Assessment and Religious Education Efforts: How to Achieve Religious Moderation in Schools? - Adrianus Adison Sihombing; Maifalinda Fatra; Abdul Quddus Suhaib; Nazar Hussain (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2023)
This study addresses the growing concern of intolerance and bias in religious education within pluralistic societies, particularly in Indonesia. It aims to examine the role of religious textbook assessment as a strategic effort to promote religious moderation in schools. The research employs a qualitative descriptive-exploratory approach, utilizing document analysis, observations, in-depth interviews, and focus group discussions with experts and assessment teams. The study analyzes 237 religious education textbooks from kindergarten to high school levels across five religions: Islam, Catholicism, Protestantism, Hinduism, and Buddhism. The findings reveal that many textbooks still contain elements of violence, bias, intolerance, and inappropriate content, with overall quality ranging from moderate to low, thus requiring substantial revision in content, presentation, language, and graphics. Textbook assessment emerges as a crucial mechanism to ensure alignment with national values, cultural diversity, and principles of tolerance and inclusivity. Furthermore, the study highlights the lack of clear guidelines and training for authors and publishers as a key challenge. This research contributes to strengthening religious moderation through educational policy and offers a practical framework for improving the quality and inclusivity of religious education materials.